2008
DOI: 10.1088/1751-8113/41/17/175101
|View full text |Cite
|
Sign up to set email alerts
|

The Signum function method for the generation of correlated dichotomic chains

Abstract: We analyze the signum-generation method for creating random dichotomic sequences with prescribed correlation properties. The method is based on a binary mapping of the convolution of continuous random numbers with some function originated from the Fourier transform of a binary correlator. The goal of our study is to reveal conditions under which one can construct binary sequences with a given pair correlator. Our results can be used in the construction of superlattices and waveguides with selective transport p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…These results are in agreement with Ref. [29], where an analytical relation between C ( ℓ ) and C sign( ℓ ) was found: C(l)=sin[π2Csign(l)] valid for γ < 1 and C ( ℓ )>0, i.e., 0.5 < α < 1. Taking into account that the correlations will be much smaller than one for large enough ℓ the sine in Eq.…”
Section: Decomposition Of a Time Series: Correlations In The Magnitudsupporting
confidence: 93%
“…These results are in agreement with Ref. [29], where an analytical relation between C ( ℓ ) and C sign( ℓ ) was found: C(l)=sin[π2Csign(l)] valid for γ < 1 and C ( ℓ )>0, i.e., 0.5 < α < 1. Taking into account that the correlations will be much smaller than one for large enough ℓ the sine in Eq.…”
Section: Decomposition Of a Time Series: Correlations In The Magnitudsupporting
confidence: 93%
“…If the series of increments {x i } is a linear Gaussian noise, Apostolov et al [23] have shown that the autocorrelation of the sign series C s ( ) can be expressed in terms of the autocorrelation C x ( ) by:…”
Section: B Relation With the Autocorrelation Of The Sign Seriesmentioning
confidence: 99%
“…In addition, |x| = |y| = √ 2/π, and σ |x| =σ |y| = 1 − (2/π). Interestingly, both C s and C m are determined exactly by C. For C s , Apostolov et al have shown [32] that…”
Section: =mentioning
confidence: 99%